APLIKASI PUPUK KASCING DAN URINE SAPI PADA MEDIUM SUBSOIL ULTISOL PADA PEMBIBITAN KELAPA SAWIT (Elaeis guineensis Jacq.) - Dwi Wulandari; Nelvia '; Sampurno ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research aims to study the effect of intraction of vermicompost fertilizer and cow urine in the medium of ultisol subsoil to growth of oil palm seedlings. The research was conducted from Maret to July 2014. The research is a factorial experiments used Completely Randomized Design (CRD), the main factor is vermicompost fertilizer with 4 levels (0, 25, 50, and 75 g/polybag) and the second factor is concentrations of cow urine with 4 levels (0, 10, 20, and 30%). Each treatments combination repeated 3 times. Parameters measured were seeds height, hump diameter, leaf numbers, dry weight of seeds, shoot and root ratio. The result showed that the application of vermicompost fertilizer and cow urine have not significant effect on seeds height, hump diameter, leaf numbers, dry weight of seeds, shoot and root ratio. The application 75 g/polybag of vermicompost fertilizer and 30% of cow urine tend to increas the seeds height, hump diameter and leaf numbers of oil palm seeds greater than other treatments. Keywords: vermicompost, cow urine, oil palm,